Polyimide varnish for highly functional conductor coatings and polyimide coatings made therefrom

By adding specific additives and dispersants to the polyimide resin, polyimide varnish with enhanced pulse durability and adhesion is prepared, which solves the problems of surface defects and carbonization of the polyimide resin during curing. It achieves efficient insulation performance and conductor adhesion, and improves productivity and thermal conductivity.

CN119220170APending Publication Date: 2024-12-31PI ADVANCED MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410836334.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-30
Filing Date
2024-06-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing polyimide resins are prone to surface defects and carbonization during the curing process, resulting in deterioration of the physical properties of the insulating coating and it is difficult to meet high productivity, excellent heat resistance, insulation properties and conductor adhesion at the same time.

Method used

Using a polyamic acid solution containing diamine monomer, dianhydride monomer, boron nitride, nanosilicon dioxide and dispersant, the surface modification of the silane coupling agent is prepared to enhance pulse durability, adhesion and improvement. Polyimide varnish with friction coefficient.

Benefits of technology

The excellent thermal conductivity, pulse durability and adhesion of the polyimide coating are achieved, the insulation performance and productivity are improved, the friction coefficient is reduced, and the adhesion to the conductor is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220170A_ABST
    Figure CN119220170A_ABST
Patent Text Reader

Abstract

Provided is a polyimide varnish comprising: a polyamic acid solution containing a diamine monomer and a dianhydride monomer as polymerization units; a first additive comprising boron nitride; a second additive comprising nanosilica; and a dispersant.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority under 35 U.S.C. §119 to Korean Patent Application No. 10-2023-0085001 filed in the Korean Intellectual Property Office on June 30, 2023, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The following disclosure relates to polyimide varnishes and polyimide coatings prepared therefrom. More particularly, the present disclosure relates to polyimide varnishes having enhanced pulse endurance, adhesion and thermal conductivity after curing and improved coefficient of friction, and polyimide coatings prepared therefrom. Background Art

[0004] The insulating layer (insulating coating) covering the conductor is required to have excellent insulating properties, adhesion to the conductor, heat resistance, mechanical strength, etc. Examples of resins that can be used for the insulating layer may include polyimide resins, polyamide-imide resins, polyester-imide resins, etc. In particular, polyimide resin among these resins is a material having excellent heat resistance and insulating properties, and has excellent properties as a material for coating the conductor.

[0005] Polyimide resin refers to a highly heat-resistant resin obtained by performing solution polymerization on aromatic dianhydride and aromatic diamine or aromatic diisocyanate to produce a polyamic acid derivative, followed by closed-loop dehydration and imidization at high temperature. The method of forming an insulating coating using a polyimide resin may include, for example, applying or coating a polyimide varnish (precursor of a polyimide resin) around a wire, and then imidizing the polyimide varnish in a curing furnace capable of performing a heat treatment at a predetermined temperature.

[0006] The method of forming the insulating coating may result in differences in the physical properties of the prepared insulating coating, productivity, and manufacturing cost, depending on conditions such as the temperature of the curing furnace, the number of coats of the polyimide varnish, and the coating speed, etc. In other words, forming the insulating coating at a high temperature may be advantageous in producing an insulating coating having excellent physical properties, and productivity may be increased due to a small number of coats or a fast coating speed.

[0007] However, when the temperature of the curing furnace is extremely high, problems such as defects on the surface of the prepared insulating coating or carbonization of the polyimide resin may occur. When the number of coatings is extremely small or the coating speed is extremely fast, the physical properties of the polyimide coating to be prepared may deteriorate. In addition, despite the excellent physical properties of ordinary polyimide resins, they do not have excellent adhesion to conductors, and therefore, problems of appearance defects may occur when forming an insulating coating.

[0008] As mentioned above, there are many difficulties in improving the properties required of polyimide varnish and polyimide resin prepared therefrom. In particular, since the improvement of one property usually leads to the reduction of other properties, it is a task that is constantly studied in the relevant technical field to meet multiple properties at the same time.

[0009] Therefore, there is a high demand for a polyimide varnish for coating a conductor, which has excellent productivity and process efficiency and satisfies the heat resistance, insulation and mechanical properties of polyimide at the same time while having excellent adhesion to the conductor as described above. Summary of the invention

[0010] Embodiments of the present invention are directed to providing a polyimide varnish having enhanced pulse durability, adhesion, and thermal conductivity after curing and an improved coefficient of friction, and a polyimide coating prepared therefrom.

[0011] Another embodiment of the present invention is directed to providing a polyimide varnish and a polyimide coating prepared therefrom for high-functional conductor coatings used in electric vehicle (EV) windings.

[0012] Various modifications can be made in the present disclosure and various embodiments can be implemented, and specific exemplary embodiments are illustrated in the drawings and described in detail. However, these exemplary embodiments are not intended to limit the present disclosure and should be understood to include all modifications, equivalents and substitutes included in the spirit and scope of the present disclosure.

[0013] The terms used in this application are only used to describe specific embodiments and are not intended to limit the present disclosure. Singular expressions include plural expressions unless the context clearly indicates otherwise. In this specification, terms such as "including" or "having" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and should not be understood as excluding the possibility of the presence or addition of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.

[0014] When amounts, concentrations, or other values ​​or parameters are given herein as ranges, preferred ranges, or lists of desired upper values ​​and desired lower values, it should be understood that all ranges formed by any pair of any upper range limit or preferred value and any lower range limit or preferred value are specifically disclosed, regardless of whether that range is disclosed individually.

[0015] Where numerical ranges are stated herein, it is intended that the endpoints of the range be within that range and that the scope of the invention not be limited to the specific values ​​stated when defining the range unless otherwise indicated.

[0016] As used herein, "dianhydride" is intended to include its precursors or derivatives, which are also referred to as "dianhydrides" or "acid dianhydrides." These products may not technically be dianhydrides, but will still react with diamines to form polyamic acids, and polyamic acids can be converted back to polyimides.

[0017] As used herein, "diamine" is intended to include precursors or derivatives thereof, which may not technically be diamines but will still react with the dianhydride acid to form a polyamic acid, and the polyamic acid can be converted back to a polyimide.

[0018] In addition, unless otherwise defined, all terms used herein, including technical or scientific terms, have the same meanings as those generally understood by those of ordinary skill in the art to which the present disclosure belongs. Terms such as those defined in common dictionaries should be interpreted as having meanings consistent with those in the context of the relevant art, and unless clearly defined in the present application, should not be interpreted in an idealized or overly formal sense. The specific details of the implementation of the present invention will be described below.

[0019] The present disclosure relates to a polyimide varnish for high-functional conductor coating and a polyimide coating prepared therefrom.

[0020] Polyimide varnish

[0021] The present disclosure provides a polyimide varnish, which includes a polyamic acid solution containing a diamine monomer and a dianhydride monomer as polymerization units; a first additive containing boron nitride; a second additive containing nano-silicon dioxide; and a dispersant.

[0022] Polyamic acid solution

[0023] The diamine monomer may include at least one selected from the group consisting of 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenyl propane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxylic acid -4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4,4'-dichloro ... 4'-Dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl) benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenyl sulfide)benzene, 1,3-bis(4-aminophenyl sulfide)benzene, 1,4-bis(4-aminophenyl sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3-bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ether )phenyl]ketone, bis[3-(4-aminophenoxy)phenyl]ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[3-(4-aminophenoxy)phenyl]sulfide, bis[4-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfide, bis[4-(4-aminophenoxy)phenyl]sulfide, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, 2-(4-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-( 4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and preferably include at least one selected from the group consisting of 1,4-diaminobenzene (PPD) and 4,4'-diaminodiphenyl ether (ODA), and more preferably include 1,4-diaminobenzene (PPD) and 4,4'-diaminodiphenyl ether (ODA). ,

[0024] The dianhydride monomer may include at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, p-phenylenebis(trimellitic acid monoester anhydride) , p-biphenylene bis(trimellitic acid monoester anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic dianhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic dianhydride, and preferably includes pyromellitic dianhydride (PMDA).

[0025] In the present disclosure, in the total dianhydride monomers, pyromellitic dianhydride (PMDA) may account for a ratio of 50 mol% or more, specifically 60 mol% or more, 70 mol% or more, 75 mol% or more, 80 mol% or more, 85 mol% or more, 90 mol% or more, 95 mol% or more, 99 mol% or more, or 100 mol% or more.

[0026] In addition, in the total diamine monomers, 4,4'-diaminodiphenyl ether (ODA) may account for a ratio of 0 to 100 mol%, specifically 50 to 95 mol%, 60 to 90 mol%, 65 to 85 mol%, 70 to 80 mol%, and 73 to 77 mol%. When 4,4'-diaminodiphenyl ether (ODA) accounts for a ratio of 0 mol%, 1,4-diaminobenzene (PPD) may account for a ratio of 100 mol%.

[0027] In addition, in the total diamine monomers, 1,4'-diaminobenzene (PPD) may account for a ratio of 0 to 100 mol%, specifically 5 to 45 mol%, 10 to 40 mol%, 15 to 35 mol%, 20 to 30 mol%, and 23 to 27 mol%. When 1,4-diaminobenzene (PPD) accounts for a ratio of 0 mol%, 4,4'-diaminodiphenyl ether (ODA) may account for a ratio of 100 mol%.

[0028] The polyamic acid solution may include the diamine monomer in an amount of 90 to 110 mol %, preferably 95 to 105 mol %, more preferably 98 to 102 mol %, and even more preferably 99 to 101 mol %.

[0029] The polyamic acid solution may include the dianhydride monomer in an amount of 90 to 110 mol %, preferably 95 to 105 mol %, more preferably 98 to 102 mol %, and even more preferably 100 mol %.

[0030] The polyamic acid solution can include dianhydride monomers of 95 to 105mol% relative to 100mol% of the diamine monomers. For example, the lower limit of the dianhydride monomer can be 95.5mol% or more, 96mol% or more, 96.5mol% or more, 97mol% or more, 97.5mol% or more, 98mol% or more, 98.5mol% or more, 99mol% or more, or 99.5mol% or more, and its upper limit can be 105mol% or less, 104mol% or less, 103mol% or less, 102mol% or less, 101mol% or less, or 100mol% or less.

[0031] The polyamic acid solution may include the dianhydride monomer and the diamine monomer in a molar ratio of about 6:4 to about 4:6.

[0032] The polyamic acid solution may further include an organic solvent.

[0033] The organic solvent may include at least one selected from the group consisting of: N,N'-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), diethylacetamide (DEAc), N-ethyl-2-pyrrolidone (NEP), N,N'-diethylformamide (DEF), dimethylpropionamide (DMPA) and γ-butyrolactone (GBL), and preferably N,N'-dimethylacetamide (DMAc).

[0034] First Additive

[0035] The polyimide varnish of the present disclosure may include a first additive including boron nitride.

[0036] The first additive may have an amount of 1 to 40 wt %, preferably 2.5 to 20 wt %, more preferably 3 to 15 wt %, and even more preferably 4 to 12 wt % relative to the weight of the solid content of the polyimide varnish.

[0037] If the amount of the first additive exceeds 40wt%, it is undesirable because the mechanical properties of the polyimide coating to be prepared may be reduced, and the amount of the additive is too large, making it difficult to achieve uniform dispersion. Meanwhile, when the amount of the first additive is less than 1wt%, it is not preferred because there is no effect of improving heat dissipation characteristics.

[0038] The first additive may have a particle size (D90) of 1 to 20 μm. For example, the lower limit may be 1.5 μm, 1.7 μm, 1.9 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.1 μm, 3.2 μm, 3.3 μm, 3.4 μm or 3.5 μm or more, and the upper limit may be 9.5 μm, 9.0 μm, 8.5 μm, 8.0 μm, 7.5 μm, 7.0 μm, 6.5 μm, 6.0 μm, 5.8 μm, 5.7 μm or 5.5 μm or less.

[0039] The boron nitride may be at least one type selected from the group consisting of cubic boron nitride (cBN), amorphous boron nitride (aBN), and hexagonal boron nitride (hBN), and is preferably hexagonal boron nitride (hBN).

[0040] Second additive

[0041] The polyimide varnish of the present disclosure may include a second additive including nano-silica.

[0042] The second additive may have an amount of 0.01 to 60 wt % relative to the weight of the solid content of the polyimide varnish. For example, the lower limit of the amount of the second additive may be 0.03 wt % or more, 0.05 wt % or more, 0.07 wt % or more, 0.1 wt % or more, 0.3 wt % or more, 0.4 wt % or more, or 0.5 wt % or more, and the upper limit thereof may be 50 wt % or less, 30 wt % or less, 10 wt % or less, 7 wt % or less, 3 wt % or less, 1.5 wt % or less, 1.2 wt % or less, or 1 wt % or less.

[0043] If the amount of the second additive exceeds 60 wt %, it is undesirable because the mechanical properties of the polyimide coating to be prepared may be degraded, and an amount of the additive less than 0.01 wt % is not preferred because pulse durability is not enhanced.

[0044] The average particle size of the second additive may be 1 to 200 nm, specifically, for example, 5 to 150 nm, 5 to 100 nm, 5 to 70 nm, 10 to 50 nm, or 10 to 30 nm. The average particle size may be measured by equipment such as BET, SEM, zeta potential analyzer, and the like.

[0045] Dispersants

[0046] The polyimide varnish of the present disclosure may include a dispersant to improve the dispersibility of the first additive.

[0047] The dispersant may include at least one selected from the group consisting of: a polyvinyl dispersant, a polyester dispersant, a polyacid ester dispersant, an unsaturated polyamide dispersant, a polyacid dispersant, a polyacid alkyl salt dispersant, a polyacrylic acid dispersant, a polyethyleneimine dispersant, and a polyurethane dispersant. Preferably, a polyurethane dispersant may be used. Due to the strong polarity of the polyurethane dispersant, the dispersibility of boron nitride may be improved.

[0048] The polyurethane-based dispersant is a dispersant having an amine value and / or an acid value, and may be a polyurethane polymer. Preferably, the polyurethane-based dispersant is a highly dispersed dispersant having only an amine value, and may be a polymer containing a urethane bond in its structure.

[0049] The dispersant may have an acid value in the range of 10 to 200 mgKOH / g or an amine value in the range of 5 to 200 mgKOH / g, but is not limited thereto.

[0050] In an embodiment, the acid value of the dispersant may be about 20 mgKOH / g or more, 30 mgKOH / g or more, 40 mgKOH / g or more, 50 mgKOH / g or more, 60 mgKOH / g or more, 70 mgKOH / g or more, 80 mgKOH / g or more, or 90 mgKOH / g or more, or may be about 190 mgKOH / g or less, 180 mgKOH / g or less, 170 mgKOH / g or less, 160 mgKOH / g or less, 150 mgKOH / g or less, 140 mgKOH / g or less, 130 mgKOH / g or less, 120 mgKOH / g or less, 110 mgKOH / g or less, or 100 mgKOH / g or less. Here, the acid value refers to a value obtained by dividing the acid group (—COOH) of the dispersant by the amount of potassium hydroxide (KOH) required for titration with KOH (a value expressed in milligrams (mg) of the amount of KOH required for titration per 1 g of the dispersant).

[0051] In an embodiment, the amine value of the dispersant may be about 10 mgKOH / g or more, about 15 mgKOH / g or more, about 20 mgKOH / g or more, 30 mgKOH / g or more, 40 mgKOH / g or more, 50 mgKOH / g or more, 60 mgKOH / g or more, 70 mgKOH / g or more, 80 mgKOH / g or more, or 90 mgKOH / g or more, or may be about 190 mgKOH / g or less, 180 mgKOH / g or less, 170 mgKOH / g or less, 160 mgKOH / g or less, 150 mgKOH / g or less, 140 mgKOH / g or less, 130 mgKOH / g or less, 120 mgKOH / g or less, 110 mgKOH / g or less, or 100 mgKOH / g or less. Here, the amine value refers to a value obtained by dividing the amino group (-NH2, -NHR or -NR2) of the dispersant by the amount of potassium hydroxide (KOH) required for titration with KOH (a value expressed in milligrams (mg) of the amount of KOH required for titration per 1 g of the dispersant).

[0052] The dispersant may have a specific gravity of 0.5 to 1.5 g / ml at 20° C. For example, the lower limit of the specific gravity of the dispersant may be 0.6 g / ml, 0.7 g / ml, 0.8 g / ml, 0.9 g / ml, or 1.00 g / ml or more. In addition, the upper limit of the specific gravity of the dispersant may be 1.4 g / ml, 1.3 g / ml, 1.2 g / ml, 1.1 g / ml, 1.07 g / ml, or 1.05 g / ml or less.

[0053] The dispersant may have an amount of 1 to 25 wt%, preferably 2.5 to 20 wt%, more preferably 3 to 15 wt%, even more preferably 3.3 to 10 wt%, and even more preferably 3.5 to 6.5 wt%, relative to the weight of the first additive.

[0054] If the amount of the dispersant is less than 1 wt %, it is undesirable because there is no effect of improving the dispersibility of the first additive, and if the amount of the dispersant is greater than 25 wt %, it is undesirable because thermal stability may be reduced.

[0055] Polyimide varnish and its cured products

[0056] The polyimide varnish may further include a silane coupling agent. The silane coupling agent may modify the surface of at least one of the first additive and the second additive. By using the silane coupling agent, surface modification may be performed to prevent aggregation of the additive in the polyimide varnish, and the functional group of the silane coupling agent may increase the interaction with the solid content (polyamic acid), thereby improving dispersibility and miscibility.

[0057] The silane coupling agent may include at least one selected from the group consisting of epoxy silane-based, alkoxy silane-based, amino silane-based, methacryloxy silane-based, isocyanate silane-based, and fluorosilane-based coupling agents, and may preferably include an epoxy silane-based coupling agent.

[0058] The epoxysilane-based coupling agent may include at least one selected from the group consisting of: (3-glycidyloxypropyl)trimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, (3-glycidyloxypropyl)methyldimethoxysilane, (3-glycidyloxypropyl)methyldiethoxysilane and (3-glycidyloxypropyl)triethoxysilane, and may preferably include (3-glycidyloxypropyl)trimethoxysilane, and OFS-6040 is more preferred among the (3-glycidyloxypropyl)trimethoxysilane products.

[0059] The amount of the silane coupling agent in the polyimide varnish may be 0.01 to 1 wt %, preferably 0.1 to 0.9 wt %, more preferably 0.3 to 0.7 wt %, and even more preferably 0.4 to 0.6 wt %.

[0060] The solid content of the polyimide varnish may be 5 to 40 wt %, preferably 10 to 38 wt %, and more preferably 12 to 35 wt %. If the solid content of the polyimide varnish is higher than the above range, it is undesirable because the polyimide varnish is difficult to use as a coating as the viscosity increases; and if it is lower than the above range, it is undesirable because a large amount of solvent needs to be removed during the curing process, which can increase manufacturing costs and process time.

[0061] The cured product of the polyimide varnish according to the present disclosure may be a film type, and the thickness of the cured product may be appropriately selected in view of use, use environment, physical properties, and the like.

[0062] In an embodiment, the polyimide varnish according to the present disclosure may have a thickness of 20 to 40 μm after curing, for example, the lower limit of the thickness may be 21 μm or more, 22 μm or more, 23 μm or more, or 24 μm or more, and the upper limit thereof may be 35 μm or less, 30 μm or less, 29 μm or less, 28 μm or less, or 27 μm or less.

[0063] In an embodiment, the polyimide varnish according to the present disclosure may have a coefficient of thermal expansion (CTE) of 20 to 30 ppm / ° C., preferably 23 to 27 ppm / ° C., and more preferably 24 to 26 ppm / ° C. after curing. The above-mentioned coefficient of thermal expansion is determined by measuring the slope in the range of 100 to 250° C. when the temperature is increased from room temperature to 350° C. at a rate of 10° C. / min using a TA thermogravimetric analyzer (TMA) Q400.

[0064] In an embodiment, the polyimide varnish according to the present disclosure may have a thermal conductivity of 0.2 to 0.8 W / mK after curing, preferably 0.23 to 0.5 W / mK, and more preferably 0.25 to 0.45 W / mK. The thermal conductivity can be determined by measuring the thermal diffusivity of the cured polyimide varnish in the thickness direction (through-plane) using a thermal conductivity meter [flash apparatus (LFA), LFA467, NETZSCH] under N2 nitrogen conditions, and calculating the thermal conductivity by multiplying the measured thermal conductivity value by the density (weight / volume) and specific heat (specific heat value measured using DSC).

[0065] In an embodiment, the polyimide varnish may have a pulse durability of 400 minutes or more, which is the time that an insulating material after curing is subjected to a certain voltage according to IEC-60851-5, wherein the pulse durability can be measured with polyimide (thickness: 26±0.5μm) under the conditions of AC 1.5kV, frequency 60Hz and leakage current upper limit 5mA. In particular, the pulse durability may be 410 minutes or more, 415 minutes or more, 420 minutes or more, 425 minutes or more, or 430 minutes or more. The above-mentioned pulse durability can be measured by fixing the film-type polyimide cured product on a fixture, applying a certain voltage to the fixed polyimide, and measuring the time when the leakage current exceeds 5mA using a withstand voltage meter (TSURUGA 8526).

[0066] In an embodiment, the polyimide varnish according to the present disclosure may have a friction coefficient (PI-PI) of 0.38 or less, preferably 0.35 or less between polyimide varnish cured products after curing. The friction coefficient can be measured using a friction coefficient tester (QM110CF, QMESYS) by fixing any one film type polyimide cured product on a pendulum and pulling it at a constant speed on another film type polyimide cured product at a load of 200 gf and a speed of 2.5 mm / s.

[0067] In an embodiment, the polyimide varnish according to the present disclosure may have a friction coefficient (PI-SUS) of 0.35 or less, preferably 0.32 or less between the cured polyimide varnish cured product and the stainless steel substrate after curing. The friction coefficient can be measured using a friction coefficient tester (QM110CF, QMESYS) by fixing the film type polyimide cured product on a pendulum and pulling it on the stainless steel substrate at a constant speed under a load of 200 gf and a speed of 2.5 mm / s.

[0068] In an embodiment, the polyimide varnish according to the present disclosure may have a peel strength of 6 N / cm or more, preferably 6.5 N / cm or more, and more preferably 7 N / cm or more after curing. The peel strength can be determined by measuring the 90° peel strength at 50 mm / sec at room temperature using a UTM (Instron model 5564) instrument, wherein the peel strength can be measured using a sample prepared by placing a film-type polyimide cured product having a thickness of 25 μm on a copper foil having a thickness of 36 μm.

[0069] In another aspect of the present disclosure, a polyimide coating including a cured product of the polyimide varnish is provided.

[0070] In an embodiment, a method of preparing a polyimide coating may include coating a polyimide varnish on a surface of a conductor; and imidizing the polyimide varnish coated on the surface of the conductor.

[0071] The conductor may be a copper wire made of copper or a copper alloy, but may also include conductors made of other metal materials, such as silver wire, etc., or various metal-plated wires, such as aluminum-plated or tin-plated wires, etc. The conductor and the coating may have a thickness according to the KSC3107 standard. The diameter of the conductor may be in the range of 0.3 to 3.2 mm, and the standard film thickness of the coating (the average of the maximum film thickness and the minimum film thickness) may be 21 to 194 μm for type 0, 14 to 169 μm for type 1, and 10 to 31 μm for type 2. Depending on the cross-sectional shape of the conductor, the conductor may be a round wire, a rectangular wire, a hexagonal wire, etc., but is not limited thereto.

[0072] In another aspect of the present disclosure, a wire including a polyimide coating is provided.

[0073] In particular, the wire may be a coated wire including a polyimide coating, prepared by coating a polyimide varnish on the surface of the wire and then imidizing it. In an embodiment, the coated wire may include a wire; and a coating in which the polyimide is coated on the surface of the wire and imidized.

[0074] In addition, the present disclosure may provide an electronic device including the coated wire. The electronic device may be, for example, a motor. BRIEF DESCRIPTION OF THE DRAWINGS

[0075] Figure 1 Surface SEM images of film-type polyimide cured products prepared by curing the polyimide varnishes of Example 1-1, Comparative Example 1-1, and Comparative Example 1-2 are shown. DETAILED DESCRIPTION

[0076] The following examples are presented to help understand the present disclosure. The following examples are provided only to make it easier to understand the present disclosure, but the content of the present disclosure is not limited to these examples.

[0077] <Example>

[0078] Example 1. Polyimide varnish

[0079] Example 1-1

[0080] A polyamic acid solution is prepared by dispersing 99.5 to 100 mol % of pyromellitic dianhydride (PMDA), which is a dianhydride compound, with 75 mol % of 4,4'-diaminodiphenyl ether (ODA) and 25 mol % of p-phenylenediamine (PPD), which are diamine compounds, in 100 mol % of N,N'-dimethylacetamide (DMAc), wherein the polyimide solid content is intended to be 13 to 25 wt %.

[0081] To the polyamic acid solution, 5wt% of a boron nitride (BN) additive (particle size (D90): 5.4μm), 0.6wt% of a nano-silica additive (average silica particle size of 10 to 20nm), 0.25wt% of a polyurethane-based dispersant (amine value of 48mgKOH / g, specific gravity (20°C) of 1.05g / ml) and 0.5wt% of an epoxy silane (OFS-6040) were added to prepare a polyimide varnish.

[0082] Example 1-2

[0083] A polyimide varnish was prepared in the same manner as Example 1-1, except that 10 wt % of a boron nitride (BN) additive and 0.5 wt % of a polyurethane-based dispersant were added instead of 5 wt % of a boron nitride (BN) additive and 0.25 wt % of a polyurethane-based dispersant in Example 1-1.

[0084] Examples 1-3

[0085] A polyimide varnish was prepared in the same manner as Example 1-1, except that 20 wt % of a boron nitride (BN) additive and 1 wt % of a polyurethane-based dispersant were added instead of 5 wt % of a boron nitride (BN) additive and 0.25 wt % of a polyurethane-based dispersant in Example 1-1.

[0086] Comparative Example 1-1

[0087] The polyimide varnish was prepared in the same manner as Example 1-1, except that the boron nitride additive, nano-silica additive, epoxy silane and polyurethane-based dispersant were not added, instead of adding the boron nitride additive, nano-silica additive, epoxy silane and polyurethane-based dispersant in Example 1-1.

[0088] Comparative Example 1-2

[0089] The polyimide varnish was prepared in the same manner as in Example 1-1, except that 5wt% of the boron nitride (BN) additive and 0.25wt% of the polyurethane-based dispersant were not added, but 3wt% of the nano-silica additive was added instead of adding 5wt% of the boron nitride (BN) additive, 0.6wt% of the nano-silica additive and 0.25wt% of the polyurethane-based dispersant in Example 1-1.

[0090] Table 1 below shows the composition and content of the polyimide varnish according to Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2. Here, in Table 1 below, the weight % (wt%) of the boron nitride additive, the nano-silica additive and the epoxy silane represents the respective amounts of the boron nitride additive, the nano-silica additive and the epoxy silane relative to the weight of the solid content of the polyimide varnish, and the wt% of the dispersant represents the total content of the dispersant relative to the total weight of the boron nitride additive.

[0091] [Table 1]

[0092]

[0093]

[0094] Example 2. Polyimide coating

[0095] Example 2-1

[0096] In a coating curing oven, an electric wire including a polyimide coating having a coating thickness of 100 μm or more was prepared by repeating the process of coating, drying and curing the polyimide varnish according to Example 1-1 on a 1 mm diameter copper wire at least 20 times.

[0097] Example 2-2

[0098] A wire including a polyimide coating having a coating thickness of 100 μm or more was prepared in the same manner as in Example 2-1, except that the polyimide varnish according to Example 1-2 was used instead of the polyimide varnish according to Example 1-1.

[0099] Example 2-3

[0100] A wire including a polyimide coating layer having a coating thickness of 100 μm or more was prepared in the same manner as in Example 2-1, except that the polyimide varnish according to Example 1-3 was used instead of the polyimide varnish according to Example 1-1.

[0101] <Experimental Example>

[0102] Experimental Example 1. Physical property evaluation

[0103] Preparation of film-type cured products of polyimide varnish for measuring physical properties

[0104] The polyimide varnish prepared in Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 was rotated at a high speed of 2,000 rpm to remove air bubbles. Then, each degassed polyimide varnish was applied to a glass substrate (230 mm x 230 mm, thickness: 0.55 mm) using a spin coater. Next, under a nitrogen atmosphere, at 110°C (20 minutes) → 150°C (20 minutes) → 200°C (20 minutes) → 300°C (20 minutes), each film type polyimide cured product was obtained by curing. Here, a film type polyimide cured product with a thickness of 26 ± 1 μm for measuring pulse durability was prepared, and a film type polyimide product with a thickness of 20 ± 1 μm for measuring other physical properties (thermal expansion coefficient, thermal conductivity, friction coefficient and peel strength) was prepared.

[0105] Figure 1 Surface SEM images of film-type polyimide cured products prepared by curing the polyimide varnishes of Example 1-1, Comparative Example 1-1, and Comparative Example 1-2 are shown.

[0106] like Figure 1 As shown, it was found that Comparative Example 1-1 had a clean surface due to the absence of the additive, while Example 1-1 and Comparative Example 1-2 had the additive visible on the surface and the dispersant well dispersed.

[0107] It can also be seen that Comparative Example 1-2 includes an excessive amount of nano-silica having a relatively small particle size, resulting in dispersion of smaller particles compared to Example 1-1 including boron nitride and nano-silica together.

[0108] (1) Coefficient of thermal expansion (CTE)

[0109] The film-type polyimide cured products prepared from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 were measured for slopes in the range of 100 to 250° C. using TA's thermogravimetric analyzer (TMA) Q400 while increasing the temperature from room temperature to 350° C. at a rate of 10° C. / min. The results are shown in Table 2.

[0110] (2) Thermal conductivity

[0111] For the film-type polyimide cured products prepared from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2, the thermal diffusivity of the cured polyimide varnish in the thickness direction (through-plane) under N2 nitrogen conditions was measured using a thermal conductivity meter [flash device (LFA), LFA467, NETZSCH], and the thermal conductivity was calculated by multiplying the measured thermal conductivity value by the density (weight / volume) and specific heat (specific heat value measured using DSC). The results are shown in Table 2.

[0112] (3) Pulse durability

[0113] The pulse durability of the film type polyimide cured product (thickness: 26±1 μm) prepared by the polyimide varnish of the above-mentioned Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 was measured using a withstand voltage meter (TSURUGA 8526) under the conditions of AC 1.5 kV, frequency 60 Hz and leakage current upper limit 5 mA. In particular, the pulse durability is determined by fixing the polyimide on a fixture, applying a certain voltage to the fixed polyimide, and measuring the time when the leakage current exceeds 5 mA. The results are shown in Table 2 below.

[0114] (4) Friction coefficient

[0115] Using a friction coefficient tester (QM110CF, QMESYS), the friction coefficient of the film type polyimide cured product prepared by the polyimide varnish of the above-mentioned embodiment 1-1 to 1-3 and the comparative embodiment 1-1 and 1-2 was measured. In particular, at a load of 200gf and a speed of 2.5mm / s, the friction coefficient of PI-PI dynamic friction was measured by fixing any film type polyimide cured product on a pendulum and pulling it at a constant speed on another film type polyimide cured product, and the friction coefficient of PI-SUS dynamic friction was measured by fixing the polyimide cured product on a pendulum and pulling it at a constant speed on a stainless steel substrate. The results are shown in Table 2 below.

[0116] (5) Peel strength

[0117] The film-type polyimide cured products prepared from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2 were measured for 90° peel strength at room temperature at 50 mm / sec using a UTM (Instron Model 5564) instrument, and the results are shown in the following Table 2. Here, the peel strength was measured using a sample prepared by placing a film-type polyimide cured product having a thickness of 25 μm on a copper foil having a thickness of 36 μm.

[0118] Table 2 below shows the results of thermal expansion coefficient (CTE), thermal conductivity, pulse durability, friction coefficient, and peel strength measurements of film-type polyimide cured products prepared from the polyimide varnishes of Examples 1-1 to 1-3 and Comparative Examples 1-1 and 1-2.

[0119] [Table 2]

[0120]

[0121] It can be confirmed from Table 2 that Examples 1-1 to 1-3 including the first additive (boron nitride), the second additive (nano-silica) and the dispersant have a thermal expansion coefficient (CTE) that is smaller than that of Comparative Examples 1-1 and 1-2, and show significantly improved thermal conductivity compared to Comparative Examples 1-1 and 1-2.

[0122] Furthermore, it can be seen that Examples 1-1 to 1-3 have significantly improved pulse durability and peel strength (adhesion), and improved friction coefficients at relatively small values.

[0123] According to these results, by appropriately combining the dispersant and the additives, a polyimide varnish having excellent thermal properties, pulse durability and adhesion as well as an improved coefficient of friction can be obtained.

[0124] The polyimide varnish and the polyimide coating including the same according to the present disclosure may include a first additive (boron nitride), a second additive (nano-silica) and a dispersant, thereby having enhanced pulse durability, adhesion and thermal conductivity, improved friction coefficient, and excellent dispersibility of the first additive and the second additive.

[0125] In addition, according to the present disclosure, pulse durability can be enhanced to increase the life of partial discharge and motor durability, and the friction coefficient can be improved to alleviate buckling when processing sharp turns and improve defects by reducing friction during stator insertion, thereby improving productivity and processability.

[0126] The present disclosure may also help improve the performance of the motor by improving thermal conductivity, thereby suppressing the temperature rise of the motor and allowing the rated current to be increased.

[0127] Furthermore, due to the enhanced adhesion, the present disclosure can achieve structural and functional reliability even in harsh environments.

[0128] In the specification, details that can be fully recognized and inferred by those skilled in the art of the present disclosure are omitted, and various modifications can be made without changing the technical spirit or basic configuration of the present disclosure, rather than within the scope of the specific embodiments described in the specification. Therefore, the present disclosure can be implemented in other ways beyond the specific description and examples herein that can be understood by those skilled in the art.

Claims

1. Polyimide varnish, comprising: a polyamic acid solution comprising a diamine monomer and a dianhydride monomer as polymerizable units; a first additive comprising boron nitride; a second additive comprising nano-silicon dioxide; as well as Dispersant.

2. The polyimide varnish according to claim 1, wherein The first additive has an amount of 1 to 40 wt % relative to the weight of the solid content of the polyimide varnish.

3. The polyimide varnish according to claim 1, wherein The second additive has an amount of 0.01 to 60 wt % relative to the weight of the solid content of the polyimide varnish.

4. The polyimide varnish according to claim 1, wherein The first additive has a particle size (D90) of 1 to 20 μm, and the second additive has an average particle size of 1 to 200 nm.

5. The polyimide varnish according to claim 1, wherein The dispersant includes at least one selected from the group consisting of polyethylene-based dispersants, polyester-based dispersants, polyacid ester-based dispersants, unsaturated polyamide-based dispersants, polyacid-based dispersants, polyacid alkyl salt dispersants, polyacrylic acid-based dispersants, polyethyleneimine-based dispersants and polyurethane-based dispersants.

6. The polyimide varnish according to claim 5, wherein The dispersant includes the polyurethane-based dispersant.

7. The polyimide varnish according to claim 1, wherein The dispersant has an amount of 1 to 25 wt % relative to the weight of the first additive.

8. The polyimide varnish according to claim 1, wherein The dianhydride monomer includes at least one selected from the group consisting of pyromellitic dianhydride (PMDA), biphenyltetracarboxylic dianhydride (BPDA), benzophenonetetracarboxylic dianhydride (BTDA), oxydiphthalic dianhydride (ODPA), diphenylsulfone-3,4,3',4'-tetracarboxylic dianhydride (DSDA), bis(3,4-dicarboxyphenyl)sulfide dianhydride, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane dianhydride, 2,3,3',4'-benzophenonetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, paraphenylene Bis(trimellitic acid monoester anhydride), p-biphenylene bis(trimellitic acid monoester anhydride), m-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, p-terphenyl-3,4,3',4'-tetracarboxylic acid dianhydride, 1,3-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)phthalic anhydride, 1,4-bis(3,4-dicarboxyphenoxy)biphenyl dianhydride, 2,2-bis[(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA), 2,3,6,7-naphthalenetetracarboxylic acid dianhydride, 1,4,5,8-naphthalenetetracarboxylic acid dianhydride and 4,4'-(2,2-hexafluoroisopropylidene)diphthalic acid dianhydride.

9. The polyimide varnish according to claim 1, wherein The diamine monomer includes at least one selected from the group consisting of: 1,4-diaminobenzene (PPD), 4,4'-diaminodiphenyl ether (ODA), 2,2-bisaminophenoxyphenyl propane (BAPP), m-phenylenediamine, 3,3'-dimethylbenzidine, 2,2'-dimethylbenzidine, 2,4-diaminotoluene, 2,6-diaminotoluene, 3,5-diaminobenzoic acid (DABA), 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-tolidine), 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 3,3'-dimethyl-4,4'-diaminodiphenylmethane, 3,3'-dicarboxy-4,4'-diaminodiphenylmethane, 3,3',5,5'-tetramethyl-4,4'-diaminodiphenylmethane, 4,4'-diaminobenzanilide, 3,3'-dimethoxybenzidine, 2,2'-dimethoxybenzidine, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminobenzophenone, 4,4'-diaminobenzophenone, 3,3'-diamino-4 ,4'-dichlorobenzophenone, 3,3'-diamino-4,4'-dimethoxybenzophenone, 3,3'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 4,4'-diaminodiphenylmethane, 2,2-bis(3-aminophenyl)propane, 2,2-bis(4-aminophenyl)propane, 2,2-bis(3-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(4-aminophenyl)-1,1,1,3,3,3-hexafluoropropane, 3,3'-diaminodiphenyl sulfoxide, 3,4'-diaminodiphenyl sulfoxide, 4,4'-diaminodiphenyl sulfoxide, 1,3-bis(3-aminophenyl)benzene, 1,3-bis(4-aminophenyl)benzene, 1,4-bis(3-aminophenyl)benzene, 1,4-bis(4-aminophenyl)benzene, 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,4-bis(3-aminophenoxy)benzene (TPE-Q), 1,3-bis(3-aminophenoxy)-4-trifluoromethylbenzene, 3,3'-diamino-4-(4-phenyl)phenoxybenzophenone, 3,3'-diamino-4,4'-di(4-phenylphenoxy)benzophenone, 1,3-bis(3-aminophenyl sulfide)benzene, 1,3-bis(4-aminophenyl sulfide)benzene, 1,4-bis(4-aminophenyl sulfide)benzene, 1,3-bis(3-aminophenyl sulfone)benzene, 1,3-bis(4-aminophenyl sulfone)benzene, 1,4-bis(4-aminophenyl sulfone)benzene, 1,3- Bis[2-(4-aminophenyl)isopropyl]benzene, 1,4-bis[2-(3-aminophenyl)isopropyl]benzene, 1,4-bis[2-(4-aminophenyl)isopropyl]benzene, 3,3'-bis(3-aminophenoxy)biphenyl, 3,3'-bis(4-aminophenoxy)biphenyl, 4,4'-bis(3-aminophenoxy)biphenyl, 4,4'-bis(4-aminophenoxy)biphenyl, bis[3-(3-aminophenoxy)phenyl]ether, bis[3-(4-aminophenoxy)phenyl]ether, bis[4-(3)-aminophenoxy)phenyl]ether, bis[4-(4-aminophenoxy)phenyl]ether, bis[3-(3-aminophenoxy)phenyl]ketone, bis[3-(4-aminophenoxy)phenyl] ketone, bis[4-(3-aminophenoxy)phenyl]ketone, bis[4-(4-aminophenoxy)phenyl]ketone, bis[3-(3-aminophenoxy)phenyl]thioether, bis[3-(4-aminophenoxy)phenyl]thioether, bis[4-(3-aminophenoxy)phenyl]thioether, bis[4-(4-aminophenoxy)phenyl]thioether, bis[3-(3-aminophenoxy)phenyl]sulfone, bis[3-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[3-(3-aminophenoxy)phenyl]methane, bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]methane 1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]methane, bis[4-(4-aminophenoxy)phenyl]methane, 2,2-bis[3-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[3-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[3-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(3-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane.

10. The polyimide varnish according to claim 1, wherein The polyamic acid solution further includes an organic solvent.

11. The polyimide varnish according to claim 10, wherein The organic solvent includes at least one selected from the group consisting of: N,N'-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), N,N'-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), diethylacetamide (DEAc), N-ethyl-2-pyrrolidone (NEP), N,N'-diethylformamide (DEF), dimethylpropionamide (DMPA) and γ-butyrolactone (GBL).

12. The polyimide varnish according to claim 1, further comprising: Silane coupling agent.

13. The polyimide varnish according to claim 1, wherein The polyimide varnish has a solid content of 5 to 40 wt %.

14. The polyimide varnish according to claim 1, wherein The coefficient of thermal expansion (CTE) after curing the polyimide varnish is 20 to 30 ppm / °C.

15. The polyimide varnish according to claim 1, wherein The thermal conductivity after curing the polyimide varnish is 0.2 to 0.8 W / mK.

16. The polyimide varnish according to claim 1, wherein The pulse durability, which is the time for which an insulating material after curing the polyimide varnish is subjected to a certain voltage according to IEC-60851-5, is 400 minutes or more.

17. The polyimide varnish according to claim 1, wherein The friction coefficient (PI-PI) between the polyimide varnish cured products after curing the polyimide varnish is 0.38 or less, and The friction coefficient (PI-SUS) between the polyimide varnish cured product after curing the polyimide varnish and the stainless steel substrate is 0.35 or less.

18. The polyimide varnish according to claim 1, wherein The peel strength after curing the polyimide varnish is 6 N / cm or more.

19. A polyimide coating comprising a cured product of the polyimide varnish according to claim 1.

20. An electric wire comprising the polyimide coating according to claim 19.

Citation Information

Patent Citations

  • Polyimide varnish and preparation method and application thereof

    CN109135554A

  • Matte polyimide black film with low heat shrinkage rate, and preparation method thereof

    CN110818928A

  • High-temperature-resistant polyimide film and preparation method thereof

    CN111704798A